INSIGHTS INTO WOMEN’S LUXURY CONSUMPTION – A TEENAGERS VERSUS YOUNG ADULTS COMPARISON - Raluca CIORNEA (Management & Marketing)
The paper aims at investigating differences in luxury consumption among female teenagers and young adults that qualify as luxury consumers. A quantitative research based on questionnaire was conducted to examine the importance given to luxury, the actual luxury consumption and the motivations that drive it. Data collection took place in a developing market, dominated by new wealth and individuals that consume premium and luxury products in a conspicuous manner, in search for social ascending validation. Results show statistical significant differences between the age groups, with adolescents exhibiting greater luxury consumption and placing a higher importance on luxury in general, and on specific categories of luxury products and services in particular. In addition, although both groups are driven in consumption by similar motivations, the social identity motivation is more prevalent for adolescents, while hedonistic reasons are wider-spread among young adults. Since no similar comparisons were found in the luxury literature, the insights provide academic and managerial implications on one of the most attractive, yet untapped, segment on the luxury market – women.